Improved LFIAs for highly sensitive detection of BNP at point-of-care - Gong Y (Dove Medical Press, 2017)
Yan Gong,1–3 Jie Hu,1,2 Jane Ru Choi,2 Minli You,1,2 Yamin Zheng,1,2 Bo Xu,4 Ting Wen,3 Feng Xu1,2 1The Key Laboratory of Biomedical Information Engineering of Ministry of Education, Department of Biomedical Engineering, School of Life Science and Technology, Xi’an Jiaotong University, 2Bioinspired Engineering and Biomechanics Center (BEBC), Xi’an Jiaotong University, 3Xi’an Diandi Biotech Company, 4School of Finance and Economics, Xi’an Jiaotong University, Xi’an, People’s Republic of China Abstract: Heart failure (HF) has become a major cause of morbidity and mortality with a significant global economic burden. Although well-established clinical tests could provide early diagnosis, access to these tests is limited in developing countries, where a relatively higher incidence of HF is present. This has prompted an urgent need for developing a cost-effective, rapid and robust diagnostic tool for point-of-care (POC) detection of HF. Lateral flow immunoassay (LFIA) has found widespread applications in POC diagnostics. However, the low sensitivity of LFIA limits its ability to detect important HF biomarkers (e.g., brain natriuretic peptide [BNP]) that are normally present in low concentration in blood. To address this issue, we developed an improved LFIA by optimizing the gold nanoparticle (GNP)–antibody conjugate conditions (e.g., the conjugate pH and the amount of added antibody), the diameter of GNP and the concentration of antibody embedded on the test line and modifying the structure of test strip. Through these improvements, the proposed test strip enabled the detection of BNP down to 0.1 ng/mL within 10–15 min, presenting ~15-fold sensitivity enhancement over conventional lateral flow assay. We also successfully applied our LFIA in the analysis of BNP in human serum samples, highlighting its potential use for clinical assessment of HF. The developed LFIA for BNP could rapidly rule out HF with the naked eye, offering tremendous potential for POC test and personalized medicine. Keywords: heart failure, biomarker, colorimetric assays, personalized medicine